Mobile social energy networks - Ong, Qing Yong (2015)
As battery usage tends to be limited to a day, there is an increasing for smartphone users need to bring along their wall charger or powerbanks on the go. This could be seen as troublesome and post as a frustration when they forget to do so and their battery goes flat. Due to such scenarios, the idea of sharing friends' charging device has been evoked so as to minimise unnecessary communication disruptions. The purpose of this project is to design and develop an android application that allow users to loan or borrow a charging device from their friends. The application will check where the user is currently located and find if there are any friends near them and have posted available charger devices for loan. Prior to the start of the project, a survey was conducted to study the user behaviour towards sharing their charging devices and the kind of charging devices they owned. Research on Android programming and Google Maps API was also done. The result of the survey showed that almost 72 percent respondents felt that sharing both their wall charger and powerbank are acceptable and almost 91 percent believe that they would share their charging device to those in need. The application is mainly coded in Java with PHP support. Lastly, the report will present the conclusion and recommendations for future work to be done.